High‐throughput techniques to evaluate the effect of ligand density for impurity separations with multimodal cation exchange resins. Issue 2 (7th October 2015) - Welsh, John P.; Bao, Haiying; Barlow, Kenneth; Pollard, Jennifer M.; Brekkan, Eggert; Lacki, Karol M.; Linden, Thomas O.; Roush, David J.
Abstract : Scale‐down, high‐throughput screening techniques are well on their way to becoming a commodity in downstream bioprocess development, especially for the rapid development of chromatography process steps. This work used both resin slurry plate and miniature column high‐throughput screening methodologies to identify the best resin properties for mAb separations utilizing a multimodal chromatography ligand interaction. A ligand with both cation exchange and hydrophobic interaction properties was studied at several ligand densities and compared to a commercially available multimodal resin with a larger particle size at high ligand density. The resins were screened with mAbs containing distinct process impurities (aggregates and a hydrophobic variant), and optimized conditions provided more than a log of clearance of both types of impurities for the different resins screened. These studies reveal that while a smaller particle size is generally preferable, optimal ligand densities can be different depending on the properties of both the mAb and impurity studied.